Infective endocarditis caused by Streptococcus tigurinus-like organisms. (September 2016) - Peuchant, O.; Wirth, G.; Tixier, R.; Dijos, M.; Camou, F.; Greib, C.; Mégraud, F.; Ménard, A.
Abstract: Streptococcus species are important causes of infective endocarditis but species identification remains challenging. We report two cases of infective endocarditis due to Streptococcus tigurinus -like organisms, which were first identified by 16S ribosomal RNA gene sequence analysis and subsequently confirmed using phylogeny based on the analysis of the shetA gene encoding exfoliative toxin.